Effective dairy extension delivery system for improved farmers' income (Indian Journal of Animal Production and Management, 2023)
The extent to which the milk production enhancement programmes succeed depends up on the extent to  which the dairy husbandry services are delivered effectively to the farmers. Basically, the dairy farmers need  three types of (integrated) support: i). Extension and advisory services (EAS) to enrich the knowledge  and improve the skills of dairy farmers ii). Availability and accessibility of input service such as semen,  vaccines, medicines, equipments, instruments, feed, fodder seeds etc and iii). Delivery of technical service  by the veterinarian (Vet) or Para-Veterinarian (Para-Vet). There are many service providers but very little  focus on EAS. Ways and means to improve the effectiveness of EAS are indicated.
Keywords: Effective delivery; Extension delivery; Dairy extension; Farmers’ income